Preparation process of polyolefin hollow fiber membrane for degassing

Through the air-cooled crystallization and stretching pore formation steps in the preparation process, a dense cortex and a high porosity inner layer are formed, which solves the problems of high water vapor transmittance and short service life of the hollow fiber membrane, and achieves low water vapor transmittance And hollow fiber membranes with high degassing efficiency, suitable for degassing treatment of ultrapure water.

CN119236701APending Publication Date: 2025-01-03HANGZHOU FAIR INNOVATIVE MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202210810870.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2022-07-11
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

The existing hollow fiber membranes have problems of high water vapor transmission and short service life in the degassing treatment of ultrapure water. In traditional processes, solvents or additives are often required to be used, which affects the quality of ultrapure water.

Method used

A process of preparing polyolefin hollow fiber membrane for degassing is adopted. Through melt extrusion, natural cooling, air-cooled crystallization and tensile stress, the cooling speed and tensile stress of the fiber are controlled to form a dense cortex and high pores. The inner layer is capable of ensuring low water vapor transmittance and high degassing efficiency of the hollow fiber membrane.

Benefits of technology

It achieves a lower water vapor transmittance and higher service life of the hollow fiber membrane, while maintaining a higher degassing efficiency, and is suitable for the preparation of ultrapure water.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119236701A_ABST
    Figure CN119236701A_ABST
Patent Text Reader

Abstract

The invention provides a preparation process of a polyolefin hollow fiber membrane for degassing, which adopts the following technical scheme: S1, spinning: a polyolefin material is subjected to melt extrusion, the melting point of the polyolefin material is Tm, and the glass-transition temperature of the polyolefin material is Tg; s2, natural cooling, wherein the surface temperature of a naturally-cooled semi-finished product obtained after natural cooling is reduced to Tm-(Tm + 20) DEG C; s3, air cooling crystallization is conducted, specifically, cooling crystallization is conducted on the naturally-cooled semi-finished product in an air blowing cooling mode, air cooling crystallization comprises a rapid cooling area and a slow cooling area, and the cooling speed of fibers in the rapid cooling area is not lower than 100 DEG C / mm (at) (100-200) m / min; and S4, stretching and pore-forming: sequentially carrying out primary shaping, cold-drawing pore-forming, hot-drawing pore-expanding and secondary shaping on the nascent fiber obtained in the step S3 to obtain the hollow fiber membrane. The thickness of a compact fiber skin layer and the porosity of a porous inner layer are controlled by limiting the cooling speed of the fibers in the air cooling crystallization step, so that the water vapor transmittance and the degassing effect of the hollow fiber membrane are accidentally better.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of membrane separation technology, and in particular to a preparation process of a polyolefin hollow fiber membrane for degassing. Background Art

[0002] Ultrapure water refers to water in which the conductive medium, non-dissociated colloids, gases and organic matter in the water are removed to an extremely low level. The characteristics of ultrapure water make it possible to be used in the preparation of various ultrapure materials (such as semiconductor materials, nano-precision ceramics, etc.). However, the preparation process of ultrapure water is relatively cumbersome. One of the steps in the preparation of ultrapure water is to remove the dissolved gases in the water body. The solubility of the gas in the water body is related to the partial pressure of the gas on the water surface, the temperature of the water body and other conditions. For example, under standard atmospheric pressure and room temperature conditions, the dissolved oxygen concentration in the water body is about 8.0-8.5ppm, and the dissolved nitrogen concentration in the water body is about 14.1ppm. Although the content of various gases dissolved in the water body is not high, in some special fields, even trace amounts of dissolved oxygen, dissolved carbon dioxide, etc. can have a greater impact.

[0003] For example, the microelectronics field has high requirements for the content of dissolved gas in ultrapure water. This is because the microelectronics field has high requirements for precision. If the dissolved oxygen in ultrapure water is too high, the dissolved oxygen reacts with the silicon wafer to form a layer of amorphous silicon oxide on the surface of the silicon wafer. This layer of amorphous silicon oxide has a great impact on the performance and yield of components. As the integration of circuits continues to increase, this impact becomes greater.

[0004] With the development of membrane separation technology, a method of removing gas from water by using a membrane contactor that combines membrane separation technology with degassing technology has emerged. Compared with traditional degassing technology, membrane separation degassing technology has the advantages of small equipment footprint, low equipment operating cost, clean and pollution-free, and no need to add various chemicals. Compared with flat membranes, hollow fiber membranes have a larger gas-liquid two-phase contact area, so they are more suitable for degassing water bodies.

[0005] There are many public documents on the preparation method of porous membrane materials. The patent with the publication number of US4247498A records that porous PP membrane materials are prepared by thermal phase separation. The patent application document with the publication number of Tsinghua University CN103464003A clearly records that the diluent and PP material are co-mixed and extruded to prepare sponge-like porous PP membrane materials. The Chinese patent application with the publication number of patent application CN107297155A discloses that on the basis of the melt-stretching method, the fibers obtained by melt spinning are rapidly cooled and the amorphous region is dissolved by solvent extraction, and a porous hollow fiber membrane with a pore structure that is connected inside and outside is obtained by further stretching and pore-forming steps. The hydrophobicity of the hollow fiber membrane provides an interface for gas-liquid contact. Only gas can be transferred from one side of the membrane to the other side, while water cannot pass through the membrane. The gas passing through the membrane is removed by vacuum purge or inert gas purge, thereby achieving the purpose of gas-liquid separation.

[0006] The above technical solutions all require the use of solvents or various additives, and a small amount of solvents or additives will inevitably remain in the final hollow fiber membrane. During the degassing process of ultrapure water, once the residual solvents or additives are dissolved, they will have a great impact on the quality of the ultrapure water. Therefore, the filter membranes produced by the above-mentioned preparation processes are not suitable for use in the field of ultrapure water preparation.

[0007] In addition, although the porous hollow fiber membrane with microporous structure that penetrates inside and outside has a good degassing effect, it is necessary to ensure that the fiber has good hydrophobicity. Once the fiber is wetted with water, the interface on the membrane surface will be destroyed, the gas-liquid separation ability will be lost, and the service life will be short. Since the microporous structure penetrates inside and outside, during the degassing process of ultrapure water, gaseous water vapor will also pass through the membrane wall, and this part of the water vapor will condense into water droplets on the vacuum equipment, which is easy to damage the vacuum equipment.

[0008] Therefore, how to prepare a hollow fiber membrane with low water vapor permeability and good degassing effect during the degassing process is a problem that needs to be solved urgently. Summary of the invention

[0009] In order to prepare a hollow fiber membrane with low water vapor permeability and good degassing effect, the present application provides a preparation process of a polyolefin hollow fiber membrane for degassing.

[0010] The present application provides a preparation process of a polyolefin hollow fiber membrane for degassing using the following technical solution:

[0011] A process for preparing a polyolefin hollow fiber membrane for degassing comprises the following process steps:

[0012] S1, spinning, melt-extrude the polyolefin material to form a semi-molded product with a hollow inner cavity under the action of a cavity-forming fluid, wherein the polyolefin material is at least one of PP, PE and PMP, and the melting point of the polyolefin material is Tm and the glass transition temperature is Tg;

[0013] S2, natural cooling, preliminarily cooling the semi-formed product obtained in step S1 by natural cooling to obtain a naturally cooled semi-finished product; the surface temperature of the naturally cooled semi-finished product obtained after natural cooling drops to Tm~(Tm+20)°C;

[0014] S3, air-cooling crystallization, cooling and crystallizing the naturally cooled semi-finished product obtained in step S2 by means of air-blowing cooling, the air-cooling crystallization includes a rapid cooling zone and a slow cooling zone, the naturally cooled semi-finished product is rolled up after passing through the rapid cooling zone and the slow cooling zone, to obtain spun fibers; wherein the surface temperature of the naturally cooled semi-finished product is reduced to (Tg+80)~(Tg+120)°C after passing through the rapid cooling zone, and the cooling rate of the naturally cooled semi-finished product in the rapid cooling zone is not less than 100°C / mm@(100~200)m / min;

[0015] S4, stretching to form holes, the primary fibers obtained in step S3 are subjected to primary shaping, cold-drawing to form holes, hot-drawing to expand holes, and secondary shaping in sequence to obtain a hollow fiber membrane.

[0016] Optionally, in step S3, the cooling rate of the naturally cooled semi-finished product in the rapid cooling zone is 100-300°C / mm@(100-300)m / min.

[0017] Optionally, in step S3, the cooling rate of the naturally cooled semi-finished product in the rapid cooling zone is 100-300°C / mm@(150-200)m / min.

[0018] By adopting the above technical solution,

[0019] In step S2, when the fiber is naturally cooled, the viscosity of the material rises rapidly as the temperature decreases, and accordingly, the dimensional stability of the fiber also rises rapidly. In addition, as the viscosity of the material increases, the macromolecular segment produces a preliminary orientation under the action of the draft stress, and it is easier to generate a lamellar structure that can be stretched into holes. Since the viscosity of the material is mainly limited by the temperature of the material, therefore, controlling the temperature of the fiber surface after natural cooling can control the amount of the fiber inner layer lamellar to a certain extent, thereby ensuring that the inner layer of the hollow fiber membrane can form a larger amount of microporous structure, so as to improve the degassing effect of the hollow fiber membrane on the basis of ensuring low water vapor permeability.

[0020] The present application limits the cooling rate of the fiber in the rapid air cooling stage to ensure that the fiber cortex thickness is low and basically maintains a dense structure during the stretching and pore-forming stage, and the inner layer of the fiber will produce a large number of microporous structures. The dense cortex structure can block the penetration of water vapor and increase the service life of the hollow fiber membrane; the low-thickness cortex and the inner layer with a large porosity can both ensure that the hollow fiber membrane has a good degassing effect. As a result, the hollow fiber membrane of the present application basically maintains a degassing efficiency similar to (or only slightly lower than) the currently common hollow fiber membranes that penetrate inside and outside, significantly lower damage sensitivity, and significantly lower water vapor permeability.

[0021] It should be noted that the cooling rate in this application is not less than 100°C / mm@(100-200)m / min, which means that when the fiber linear speed is 100-200m / min, the temperature reduction value is not less than 100°C in a cooling path of 1mm.

[0022] Furthermore, the present application specifically divides air-cooled crystallization into two sections with different cooling rates. After passing through the rapid cooling zone, the fiber quickly enters the slow cooling zone. The fiber cooling rate in the slow cooling zone slows down, and the heat exchange rate between the fiber and the outside world is significantly reduced. The cortex is no longer thickened due to rapid cooling. Therefore, the thickness of the cortex formed by the fiber accounts for a lower proportion of the membrane wall thickness, and the degassing efficiency of the hollow fiber finally obtained is less affected.

[0023] The reason why the cooling rate of the fiber in the slow cooling zone is significantly reduced may be that the cortex of the fiber solidifies quickly in the rapid cooling zone, and the solid cortex hinders the heat exchange between the inner layer of the fiber and the outside world; combined with the decrease in the temperature difference between the fiber and the outside world after the fiber enters the slow cooling zone, the heat exchange rate between the fiber and the outside world is significantly reduced.

[0024] In addition, the specific two-stage air-cooled crystallization can form a sudden change in temperature in the direction of the fiber wall thickness, rather than the conventionally known gradual temperature gradient. Among them, the temperature of the fiber cortex is lower and the temperature gradient in the direction of the cortex wall thickness is smaller; the temperature of the fiber inner layer is higher and the temperature gradient in the direction of the wall thickness is smaller. That is, the fiber is divided into two relatively uniform temperature distribution areas inside and outside. Although the temperature distribution in each area is relatively uniform, the temperature difference between the two areas is large. This means that each area of ​​the fiber inner layer has a uniform and slow cooling rate. Therefore, the macromolecular chain segments in each part of the fiber inner layer are more active, which facilitates nucleation and crystal growth in all parts of the fiber inner layer.

[0025] Since the nucleation and crystal growth behaviors in various parts of the fiber inner layer are relatively uniform, the pore size of the micropores formed in the fiber inner layer during the stretching and pore-forming step is relatively small in the direction of the wall thickness, rather than forming obvious gradient pores. The relatively uniform microporous structure of the fiber inner layer can more quickly guide the gas passing through the dense cortex, thereby improving the degassing effect of the hollow fiber membrane. It should be noted that the so-called small difference in the pore size of the micropores in the direction of the skin thickness refers to the small change in the pore size of the micropores in the inner layer along the wall thickness direction. For example, the size of the micropores close to the hollow cavity is roughly the same as the size of the micropores close to the cortex, with little change.

[0026] It should be noted that during the air-cooled crystallization stage, the fiber cannot be cooled continuously and rapidly, otherwise the ratio of the skin thickness to the membrane wall thickness will be too high, or even the entire membrane wall will be cooled rapidly, resulting in low crystallinity of the entire membrane wall. This is one of the important reasons why this application does not adopt cooling methods such as liquid rapid extraction and cooling.

[0027] The above limitation is unexpected for the following reasons. It is expected that the service life of the hollow fiber membrane with a dense cortex will be improved and the water vapor permeability will be reduced, but it must be at the expense of a significant reduction in degassing efficiency. This is because the diffusion mechanism of gas on the dense cortex is a permeation mechanism. Under the same conditions, the permeation rate of the gas must be lower than the diffusion rate of the gas in the pore structure. Therefore, the degassing efficiency of the hollow fiber membrane with a dense cortex must be lower than the degassing efficiency of the hollow fiber membrane that is connected inside and outside. In addition, it can also be expected that there must be a gradient change in temperature on the fiber wall thickness during rapid cooling, and it should be a more continuous form of change, rather than a gradient change.

[0028] However, the present application shows that, by controlling the cooling rate of the fiber cortex and adding a slow cooling zone after rapid cooling, a cortex with high density but low thickness and an inner layer with high porosity and insignificant radial changes in pore structure can be obtained. This means that even if a dense cortex structure is introduced into the hollow fiber membrane, it not only has a significantly lower damage sensitivity and lower water vapor permeability, but also unexpectedly has a degassing efficiency that is substantially the same (or only slightly lower) than that of the current hollow fiber membrane that is connected inside and outside. This shows that the hollow fiber membrane preparation process in the present application is a completely different design strategy.

[0029] Optionally, in step S1, the die temperature during melt extrusion is (Tm+10) to (Tm+70)°C; the die aspect ratio during spinning is 2 to 5; and the crystallinity of the polyolefin material is not less than 40%.

[0030] By adopting the above technical solution, the crystallinity of polyolefin and the die head temperature during melt extrusion are coordinated to greatly affect the final crystallinity of the inner layer of the primary fiber and the orientation of the lamellae. This is because the die head temperature and crystallinity during melt extrusion synergistically affect the viscosity of polyolefin. When the die head temperature during melt extrusion is (Tm+10)~(Tm+70)℃ and the crystallinity is not less than 40%, the polyolefin material has a more suitable viscosity. Under the premise of the same traction force, the polyolefin material with suitable viscosity can obtain greater tensile stress, and accordingly, the macromolecular chain orientation of the fiber is higher, and the inner layer of the fiber can form more pore structures, thereby improving the degassing efficiency of the hollow fiber membrane.

[0031] The die aspect ratio during spinning must also be strictly limited. The smaller the die aspect ratio, the smaller the free volume of the extruder, the greater the outlet expansion effect, the smaller the shear force on the material in the pore, the less regular structure formed, the lower the crystallinity, and thus affects the porosity of the membrane. The pore expansion phenomenon, also known as the Balas effect, refers to the fact that when a polymer fluid is extruded from a small hole, capillary or slit, the diameter or thickness of the extrudate will be significantly larger than the size of the pore.

[0032] The present application specifically limits the die head aspect ratio to 2 to 5. When the molten polyolefin material flows in the spinneret hole, the macromolecular chains are oriented by the shear force. The larger the aspect ratio, the longer the solution is subjected to the shear force, making the arrangement of the macromolecular chains more regular. The regular macromolecules formed under the shear action in the hole are not easy to lose their regular structure due to the swelling of the hole mouth.

[0033] It should be noted that the above-mentioned crystallinity of not less than 40% is the crystallinity measured by the DSC method.

[0034] Optionally, in step S2, the length of the natural cooling path is 30 to 1000 mm; the atmosphere during natural cooling is air or nitrogen, and the atmosphere temperature during natural cooling is 40 to 70°C; the cooling rate of the surface of the semi-molded product during natural cooling is (0.05 to 0.6)°C / mm@(100 to 200)m / min.

[0035] By adopting the above technical scheme, the natural cooling path length, atmosphere temperature and cooling rate of the fiber surface during natural cooling need to be strictly controlled. This is because the cooling behavior of the fiber during natural cooling greatly affects the magnitude and uniformity of the tensile stress on the fiber, and tensile stress is an important influencing factor of lamellar growth and orientation.

[0036] If the natural cooling rate is too slow, the polyolefin material maintains a low viscosity for a long time, the tensile stress it is subjected to is reduced, and the crystallization dynamics of the polyolefin material are insufficient, resulting in low crystallinity and crystal orientation of the inner layer of the spun fiber; if the natural cooling rate is too fast, although the tensile stress of the fiber becomes larger, the tensile stress is too concentrated, the uniformity of the tensile stress becomes worse, and the crystallinity and crystal orientation of the spun fiber are also low.

[0037] Optionally, in step S1, the polyolefin material is PP; the isotacticity of PP is not less than 95%; the melt index of PP is 1-7 g / min@(190°C, 5kg); the crystallinity of PP is 45-70%; and the wall thickness of the semi-molded product is 0.5-3 mm.

[0038] Optionally, in step S1, the isotacticity of PP is not less than 99%; and the melt index of PP is 2 to 5 g / min@(190° C., 5 kg).

[0039] By adopting the above technical solution, PP is a polyolefin material with good performance, which is very suitable for preparing hollow fiber membranes for degassing. However, not all PP materials are suitable for the preparation process in this application. If the crystallinity of PP is too low, it is difficult for the inner layer of the hollow fiber membrane to form sufficient porosity during the stretching and pore-forming stage, and the degassing effect is poor; if the crystallinity of PP is too high, firstly, the cortex of the hollow fiber membrane is also prone to produce pore structure, and secondly, the inner layer porosity and pore size of the hollow fiber membrane are too large, which leads to the reduction of its mechanical properties and service life, and the water vapor permeability will also increase.

[0040] The melt index of PP is a value that indicates the fluidity of the material during processing. The larger the melt index value, the better the processing fluidity of the material, and vice versa. When the melt index is small, the obstacle to the rearrangement of the molecular chain increases, and the activation energy required for the molecular chain to diffuse to the crystal nucleus increases, thereby reducing the crystallinity. When the melt index is large, the plasticity of the material deteriorates and it is difficult to form.

[0041] The present application defines the melt index of PP as 1-7 g / min, preferably 2-5 g / min, which can ensure that the hollow fiber membrane has a dense skin layer and an inner layer with a high porosity, thereby improving the degassing effect while increasing the service life and reducing the water vapor transmission rate.

[0042] Optionally, in step S1, the die temperature during melt extrusion is 180-200°C;

[0043] In the step S2, the surface temperature of the naturally cooled semi-finished product obtained after natural cooling is 168-178° C.;

[0044] In step S3, the surface temperature of the naturally cooled semi-finished product after passing through the rapid cooling zone is 80-100°C.

[0045] By adopting the above technical scheme, when the polyolefin material is PP, the melt extrusion temperature and the temperature of the fiber surface after natural cooling are specifically limited, so that the PP can obtain a larger and more uniform tensile stress during melt extrusion and natural cooling, promote the crystallization and lamella orientation of PP, and improve the crystallinity and crystallization orientation of the inner layer of the primary fiber; the temperature of the fiber surface after passing through the rapid cooling zone is specifically limited, which can ensure that the fiber cortex no longer produces crystallization behavior after passing through the rapid cooling zone, and the inner layer of the fiber still has a relatively slow cooling rate even after passing through the rapid cooling zone, so that the inner layer of the fiber has enough time to obtain lamellae of sufficient size and form lamella orientation under the action of the drawing stress.

[0046] The above three process parameters work together to limit the temperature of the fiber surface at multiple stages, so that a hollow fiber membrane with a dense skin and low thickness, a large inner porosity and a small difference in pore size inside and outside the pores can be obtained, and the hollow fiber membrane can have a long service life, low water vapor permeability and high degassing efficiency.

[0047] Optionally, in step S3, the winding speed is 100-200 m / min; and the nozzle stretching ratio is 10-50.

[0048] By adopting the above technical solution, the winding speed has a great influence on the cooling speed of the fiber in the natural cooling stage and the air cooling stage. If other cooling conditions are the same, the faster the winding speed, the slower the cooling speed; the nozzle draft ratio has a great influence on the tensile stress of the fiber. The larger the nozzle draft ratio, the greater the tensile stress of the fiber. Therefore, it is necessary to control the winding speed and nozzle draft ratio to obtain a more suitable fiber cooling speed and fiber draft stress, so that the obtained primary fiber has a better crystal distribution state.

[0049] Optionally, in step S3, the speed of the cooling air flow is 25-35% of the winding speed; the temperature of the cooling air flow is 40-70°C.

[0050] By adopting the above technical solution, the speed and temperature of the cooling airflow need to match the winding speed of the fiber. The faster the fiber winding speed, the faster the cooling airflow should be, so that the cooling speed of the fiber surface can be controlled to be not less than 100℃ / mm@(100~200)m / min. The hollow fiber finally obtained can have a better pore distribution and a more suitable skin thickness.

[0051] Optionally, in step S3,

[0052] The wind direction of the cooling airflow is inclined along the conveying direction of the naturally cooled semi-finished product; the angle formed by the wind direction of the cooling airflow and the axis of the naturally cooled semi-finished product is 30 to 70 degrees; the path length of the slow cooling zone is 4 to 8 meters.

[0053] By adopting the above technical solution, the inventor unexpectedly discovered that compared with setting the cooling airflow to be perpendicular to the fibers to sweep the fibers, setting the cooling airflow direction to form a certain angle with the fibers can obtain a hollow fiber membrane with higher dimensional stability, lower skin thickness and better pore structure.

[0054] This may be because after the polyolefin material is melted and extruded and naturally cooled, its temperature is still above the melting point. If the air is blown vertically, the fiber will be greatly disturbed by the cooling airflow and easily shake, resulting in a decrease in dimensional stability. However, setting the direction of the cooling airflow to be in the same direction as the fiber conveying direction and forming a certain angle can greatly reduce the disturbance of the cooling airflow on the fiber, thereby improving the stability of the fiber size.

[0055] In addition, in order to avoid the problem of excessive cortical thickness and excessive cooling of the inner layer of the fiber, which leads to a decrease in crystallinity, it is necessary to avoid further rapid cooling of the fiber surface. The specific cooling airflow direction of the present application is set so that the temperature of the cooling airflow rises after rapid heat exchange with the fiber in the rapid cooling zone. Since the wind direction of the cooling airflow is the same as the fiber conveying direction and is at a certain angle, the heated cooling airflow will continue to blow a certain distance in the direction of fiber conveying, thereby forming an air film on the fiber surface with a higher temperature than the environment, so as to reduce the cooling rate of the fiber in the slow cooling zone, reduce the cortical thickness of the fiber, and increase the porosity of the inner layer.

[0056] The path length of the slow cooling zone is limited to ensure that the inner layer of the fiber has enough time for crystallization and lamellar orientation after passing through the rapid cooling zone and before winding.

[0057] Optionally, the cold drawing rate is (10-30)% / min; the cold drawing elongation is 20-40%; the cold drawing temperature is (Tg-30)-(Tg+80)°C; the hot drawing rate is not higher than 15% of the cold drawing rate; the hot drawing elongation is 2-6 times the cold drawing elongation; and the hot drawing temperature is (Tm-60)-(Tm-30)°C.

[0058] By adopting the above technical solution,

[0059] The hot and cold drawing process also has a very important influence on the thickness and density of the hollow fiber membrane skin and the pore structure of the inner layer.

[0060] This application specifically adopts a cold drawing process with less pulling and faster pulling in combination with a hot drawing process with more pulling and slower pulling, so that the inner layer has a higher porosity and a better pore structure. The main function of cold drawing is to pull the lamellae apart and form an initial microfiber lacing structure and pore structure; the main function of hot drawing is to further pull apart the lamellae that have not been pulled apart in the cold drawing stage, and to expand the micropores generated in the cold drawing stage. Therefore, cold drawing and hot drawing are interrelated and mutually influential processes, and there is a high degree of correlation between the process parameters of the two. They are not two isolated steps. When adjusting the process parameters, the overall process parameters of the two must be adjusted uniformly.

[0061] For example, the hot drawing rate must be adapted to the cold drawing rate. This is because different cold drawing rates produce different pore structures, different internal residual stress conditions, different degrees of separation of lamellae and different structures of microfiber bands. These conditions will affect the hot drawing rate. Therefore, the cold drawing rate or the hot drawing rate cannot be adjusted in isolation.

[0062] Similarly, the hot stretch elongation and cold stretch elongation must also be compatible. The degree of lamellar separation in the fiber inner layer, the length and thickness of the microfiber bands, etc. are all different under different cold stretch elongation. Correspondingly, the hot stretch elongation also needs to be adjusted based on the fiber structure caused by different cold stretch elongation. When the ratio of hot stretch elongation to cold stretch elongation is too small, it means excessive cold stretching and / or insufficient hot stretching; when the ratio of hot stretch elongation to cold stretch elongation is too large, it means insufficient cold stretching and / or excessive hot stretching, both of which may lead to deterioration of the pore structure.

[0063] Optionally, in step S4, the primary setting temperature is (Tm-60) to (Tm-20)°C; the primary setting time is 25 to 35 min; the primary fiber is stretched during the primary setting process, and the stretching elongation is 0.5 to 2%; the secondary setting temperature is higher than the primary setting temperature, and the difference between the two is 10 to 20°C; the secondary setting time is 0.5 to 3 min.

[0064] By adopting the above technical solution, the primary shaping process and the secondary shaping process have a greater impact on the performance of the hollow fiber membrane finally obtained.

[0065] Among them, the one-time shaping process determines the crystallinity, crystal form, orientation and size of the fiber before stretching and hole forming, and the one-time shaping can eliminate the structural defects in the primary fiber, improve the structural integrity of the fiber, and reduce the possibility of excessive concentration of tensile stress in the subsequent stretching and hole forming process.

[0066] The present application specifically applies a small amount of external drawing force to the fiber (drawing elongation is about 1%) and reduces the time for one setting. This is because a small amount of external drawing force can reduce the thermal expansion of the fiber at high temperature, and a small amount of external drawing force can promote the orientation of the lamellae and improve the regularity and orientation of the lamellae. The specifically reduced one-time setting time can reduce the possibility of cortical nucleation, crystal growth and orientation under high temperature and external drawing stress. Thereby reducing the possibility of the cortex forming a pore structure in the subsequent stretching and pore-forming step.

[0067] In addition, it should be noted that although a small amount of stretching force is applied in this application, once the temperature during the primary shaping process is too high, some of the lamellae melt, and a small amount of stretching stress is not enough to make them grow into lamellae during recrystallization. Therefore, in the primary shaping step, the temperature, time, and applied stretching force affect and constrain each other.

[0068] In addition, the present application limits the secondary setting temperature to 10 to 20°C higher than the primary setting temperature, and specifically limits a shorter secondary setting time. This is because the inventor unexpectedly discovered that in the system of the present application, this temperature and this processing time can effectively eliminate the residual stress in the stretching and pore-forming stage without destroying the lamellar crystals and pore structure (too high temperature, too long processing time, etc. can easily cause melt recrystallization of thin lamellar crystals and microfiber tie structures, thereby causing destruction of the lamellar structure and pore structure; too low temperature can easily cause fiber shrinkage, resulting in deterioration of the pore structure).

[0069] In summary, the present application includes at least one of the following beneficial technical effects:

[0070] 1. By dividing the rapid air cooling into a rapid cooling zone and a slow cooling zone, and limiting the cooling rate of the fiber, a dense but thin skin layer and an inner layer with high porosity can be obtained. The hollow fiber membrane with the above-mentioned specific structure not only has lower damage sensitivity and lower water vapor permeability, but also has a degassing effect that is only slightly lower than that of a porous hollow fiber membrane (microporous structure penetrating inside and outside).

[0071] 2. By limiting the speed, temperature, angle, etc. of the cooling air flow, not only can the fiber reach the required cooling rate in the fast cooling zone, but also ensure that the fiber has a lower cooling rate in the slow cooling zone. At this time, the fiber surface does not crystallize and the internal cooling is slow, so there is enough time for nucleation and crystal growth, thereby obtaining a suitable cortex and inner layer.

[0072] 3. By adopting a specific rapid cold drawing and slow hot drawing stretching pore-forming process and correlating the process parameters of cold drawing pore-forming and hot drawing pore-forming, it can ensure that the cortex of the hollow fiber membrane has a dense structure and the inner layer has a good pore structure; to ensure that the hollow fiber membrane has a long service life, low water vapor permeability and high degassing effect.

[0073] 4. By limiting the primary shaping process parameters and the secondary shaping process parameters and correlating the process parameters of the two, it can be ensured that the hollow fiber membrane finally produced has better pore structure and mechanical properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0074] Figure 1 This is a SEM image of the outer surface of the hollow fiber membrane prepared in Example 3 of the present application, and the magnification is 10000X.

[0075] Figure 2 This is a SEM image of the inner surface of the hollow fiber membrane prepared in Example 3 of the present application, and the magnification is 10000X.

[0076] Figure 3 This is a SEM image of the outer surface of the hollow fiber membrane prepared in Comparative Example 2 of the present application, and the magnification is 10000X.

[0077] Figure 4 This is a SEM image of the inner surface of the hollow fiber membrane prepared in Comparative Example 2 of the present application, and the magnification is 10000X. DETAILED DESCRIPTION

[0078] The following is combined with Figures 1 to 4 This application is described in further detail.

[0079] Unless otherwise specified, in the following examples, the raw materials and equipment used to prepare the hollow fiber membranes can be purchased from commercial sources. The structure and morphology of the membranes were characterized using a scanning electron microscope (S-5500) provided by Hitachi.

[0080] It should be noted that since the hollow fiber membrane prepared in this application is mainly used in the degassing step in the ultrapure water preparation process (of course, it can also be applied to degassing in other fields), due to the characteristics of ultrapure water, the seepage effect of the hollow fiber membrane needs to be strictly controlled. For example, when preparing hollow fiber membranes by methods such as thermally induced phase separation and liquid cold extraction, solvents need to be used, and some of the solvents must remain in the prepared hollow fiber membranes (even after post-treatment and desolvation). This part of the solvent is likely to seep out during the ultrapure water degassing treatment, resulting in ultrapure water contamination. For example, in order to obtain better mechanical properties, various additives such as fillers, nucleating agents, etc. are added to polyolefin materials. Similarly, although the above-mentioned additives can improve the mechanical properties of the prepared hollow fiber membranes to a certain extent, the risk of impurity seepage is contrary to the purpose of this application.

[0081] On the basis of the above, the embodiment of the present application discloses a preparation process of a polyolefin hollow fiber membrane for degassing. Preferably, the hollow fiber membrane can be used for degassing of ultrapure water.

[0082] Example 1

[0083] In this embodiment, the polyolefin material is PE, and more preferably, commercially available mLLDPE (metallocene linear low-density polyethylene) is used. The crystallinity of mLLDPE is 68% (measured by DSC method) and the density is 0.93 g / cm 3 , molecular weight is 60,000, molecular weight distribution index is about 2.3, melt index is 4.5g / min@(130℃, 5kg). In addition, the melting point Tm of mLLDPE is about 119℃, and the glass transition temperature Tg is about -38℃.

[0084] The preparation process of the hollow fiber membrane for degassing using the above mLLDPE as raw material comprises the following process steps:

[0085] S1, spinning, put the above mLLDPE into an extruder for melt mixing, melt mixing includes melting, mixing and metering in sequence, and the temperature is set to 135°C, 125°C and 150°C respectively. After melt mixing is completed, the molten material is extruded into fibers, and a vertical downward spinning extrusion method is adopted. A hollow die head is used during extrusion, and a cavity fluid is injected into the hollow inner cavity of the die head. In this embodiment, the cavity fluid is nitrogen (the cavity fluid can also be other inert gases, or even liquid fluids), and the outlet wall thickness of the material on the die head is 2mm (that is, the wall thickness is 2mm when extruded into fibers). The die head temperature is 140°C, and the die head aspect ratio is 5. Under the action of the cavity fluid, the material is extruded to form a semi-molded product with a hollow inner cavity. At this time, the semi-molded product is liquid.

[0086] S2, natural cooling, the semi-molded product obtained by extruding the molten material is exposed to the air (of course, the atmosphere can also be controlled to be an inert gas such as nitrogen) for preliminary natural cooling, and is naturally cooled until the surface temperature of the fiber is about 125°C, and the natural cooling is completed to obtain a naturally cooled semi-finished product. The natural cooling path length is controlled to be 300mm, and the temperature of the atmosphere around the semi-molded product is controlled to be 70°C, and the cooling rate of the fiber surface is about 0.05°C / mm@(120m / min).

[0087] S3, air cooling crystallization, after the fiber surface is cooled to a temperature close to the melting point of the material to obtain a naturally cooled semi-finished product, the fiber is further cooled by blowing cooling to cause the fiber to undergo cooling crystallization. In this step, the speed of the cooling airflow is 33m / min, the temperature of the cooling airflow is 70°C, the wind direction of the cooling airflow is inclined toward the direction of fiber conveying, and the angle formed by the wind direction of the cooling airflow and the axis of the fiber is 60°.

[0088] It should be noted that the air-cooling crystallization in this step is divided into two sections, namely the rapid cooling zone and the slow cooling zone. The area where the cooling airflow moves along its wind direction and directly contacts the fiber is considered to be the rapid cooling zone. The cooling airflow and the fiber produce rapid heat exchange in this area, so that the surface of the fiber is rapidly cooled; the area from the fiber passing through the rapid cooling zone to the winding is considered to be the slow cooling zone. After the fiber passes through the rapid cooling zone and the slow cooling zone in turn, it is wound to obtain the nascent fiber.

[0089] After the fiber passes through the rapid cooling zone, the surface temperature drops to about 80°C, and then passes through the slow cooling zone with a path length of 6m for winding. The winding speed is 120m / min (i.e., spinning speed), and the nozzle stretch ratio is 40. The cooling rate of the fiber in the rapid cooling zone is 150°C / mm@(120m / min).

[0090] It should be noted that the boundary between the rapid cooling zone and the slow cooling zone is determined based on the cooling rate of the fiber surface. When the cooling rate of the fiber surface decreases significantly, it is considered that the fiber has entered the slow cooling zone from the rapid cooling zone.

[0091] S4, stretching to form holes, stretching to form holes includes primary shaping, cold drawing to form holes, hot drawing to expand holes and secondary shaping in sequence, that is, step S4 specifically includes the following process steps:

[0092] S41, primary setting, subjecting the wound spun fibers to a first heat setting treatment, the heat setting temperature being 95°C, the heat setting time being 30 minutes, during the heat setting process, applying an external force to the spun fibers for stretching, and the stretching elongation being 1%. After the first heat setting treatment of the spun fibers, a heat-set semi-finished product is obtained.

[0093] S42, cold drawing to cause pores. After the primary fiber has been subjected to the first heat setting treatment, the defects in the fiber are roughly eliminated. At this time, the fiber can be cold drawn to initially produce a microporous structure in the inner layer with a high degree of fiber crystallinity. In the cold drawing to cause pores stage, a single cold drawing process is adopted, with a cold drawing elongation of 30%, a cold drawing rate of 20% / min, and a cold drawing temperature of 25°C. After cold drawing, a cold drawn semi-finished product is obtained.

[0094] S43, hot drawing and hole expansion. After the fiber is cold drawn, the inner layer of the lamellae is separated and a microporous structure is generated. The fiber can be further hot drawn to expand the generated microporous structure. In addition, hot drawing can further pull apart the lamellae that have not been separated during the cold drawing process, thereby generating a larger number of microporous structures in the inner layer of the fiber. In the hot drawing and hole expansion stage, a hot drawing process is used, the hot drawing elongation is 100%, the hot drawing rate is 2% / min, the hot drawing temperature is 85°C, and a hot drawing semi-finished product is obtained after hot drawing.

[0095] S44, secondary shaping, after the fiber is cold and hot drawn, the microporous structure of the inner layer is basically formed, but once the drawing force is removed, the fiber is easy to shrink, resulting in a reduction in the microporous structure or even partial closure. Therefore, the fiber needs to be heat-set for the second time after the cold and hot drawing treatment. In the second heat setting stage, the heat setting temperature is 115°C, the heat setting time is 1.5 minutes, and the hollow fiber membrane is obtained by natural cooling after the heat setting is completed.

[0096] Example 2

[0097] In this embodiment, the polyolefin material is PMP, which is purchased from Mitsui of Japan and has a brand name of TPX. The crystallinity of TPX is 55% (measured by DSC method) and the density is 0.83 g / cm 3 , molecular weight is 98,000, molecular weight distribution index is 3.2, Vicat softening temperature is 165°C, melt index is 5g / min@(240°C, 5kg). In addition, the melting point Tm of TPX is about 240°C, and the glass transition temperature Tg is 28°C.

[0098] The preparation process of the hollow fiber membrane for degassing using the above TPX as raw material includes the following process steps:

[0099] S1, spinning, put the above TPX into the extruder for melt mixing, melt mixing includes melting, mixing and metering in sequence, and the temperatures are set to 250°C, 265°C and 260°C respectively. After melt mixing, the molten material is extruded into fibers, and a vertical downward spinning extrusion method is adopted. A hollow die is used during extrusion, and a cavity-forming fluid is injected into the hollow inner cavity of the die. In this embodiment, the cavity-forming fluid is nitrogen, and the outlet wall thickness of the material on the die is 2mm (that is, the wall thickness is 2mm when extruded into fibers). The die temperature is 255°C, and the die aspect ratio is 4. Under the action of the cavity-forming fluid, the material is extruded to form a semi-molded product with a hollow inner cavity. At this time, the semi-molded product is still in liquid state.

[0100] S2, natural cooling, the semi-molded product obtained by extruding the molten material is exposed to the air for preliminary natural cooling, and is naturally cooled until the surface temperature of the fiber is about 245°C, and the natural cooling is completed to obtain a naturally cooled semi-finished product. The natural cooling path length is controlled to be 100mm, and the temperature of the atmosphere around the semi-molded product is controlled to be 50°C, and the cooling rate of the fiber surface is about 0.1°C / mm@(150m / min).

[0101] S3, air cooling crystallization, further cooling the fiber by blowing cooling to make the fiber undergo cooling crystallization. In this step, the speed of the cooling airflow is 52 m / min, the temperature of the cooling airflow is 70°C, the wind direction of the cooling airflow is inclined toward the direction of fiber conveying, and the angle formed by the wind direction of the cooling airflow and the axis of the fiber is 45°.

[0102] It should be noted that the air-cooling crystallization in this step is divided into two sections, namely the rapid cooling zone and the slow cooling zone. The area where the cooling airflow moves along its wind direction and directly contacts the fiber is considered to be the rapid cooling zone. The cooling airflow and the fiber produce rapid heat exchange in this area, so that the surface of the fiber is rapidly cooled; the area from the fiber passing through the rapid cooling zone to the winding is considered to be the slow cooling zone. After the fiber passes through the rapid cooling zone and the slow cooling zone in turn, it is wound to obtain the nascent fiber.

[0103] After the fiber passes through the rapid cooling zone, the surface temperature drops to about 130°C, and then passes through the slow cooling zone with a path length of 7m for winding. The winding speed is 150m / min (i.e., spinning speed), and the nozzle stretch ratio is 40. The cooling rate of the fiber in the rapid cooling zone is 230°C / mm@(150m / min).

[0104] It should be noted that the angle between the cooling airflow and the fiber is different, and the width of the rapid cooling zone also changes slightly. Therefore, the boundary between the rapid cooling zone and the slow cooling zone is determined based on the cooling rate on the fiber surface. When the cooling rate on the fiber surface decreases significantly, it is considered that the fiber has entered the slow cooling zone from the rapid cooling zone.

[0105] S4, stretching to form holes, stretching to form holes includes primary shaping, cold drawing to form holes, hot drawing to expand holes and secondary shaping in sequence, that is, step S4 specifically includes the following process steps:

[0106] S41, primary setting, subjecting the wound spun fibers to a first heat setting treatment, the heat setting temperature being 180°C, the heat setting time being 25 minutes, during the heat setting process, applying an external force to the spun fibers for stretching, and the stretching elongation is 1.5%. After the first heat setting treatment of the spun fibers, a heat-set semi-finished product is obtained.

[0107] S42, cold drawing to form holes. In the cold drawing to form holes stage, a single cold drawing process is adopted, the cold drawing elongation is 25%, the cold drawing rate is 15% / min, the cold drawing temperature is 35°C, and a cold drawn semi-finished product is obtained after cold drawing.

[0108] S43, hot drawing and hole expansion. In the hot drawing and hole expansion stage, a one-time hot drawing process is adopted, the hot drawing elongation is 150%, the hot drawing rate is 1.2% / min, the hot drawing temperature is 180°C, and the hot drawn semi-finished product is obtained after hot drawing.

[0109] S44, secondary shaping, in the second heat setting stage, the heat setting temperature is 200°C, the heat setting time is 1 minute, and after the heat setting is completed, the hollow fiber membrane is obtained by natural cooling.

[0110] Example 3

[0111] In this embodiment, the polyolefin material is PP, preferably isotactic homopolymer PP, the crystallinity of the PP is 50% (measured by DSC method), the isotacticity is 99.9%, the molecular weight is about 80,000, the molecular weight distribution index is 1.5, and the melt index is about 2g / min@(190°C, 5kg). In addition, the melting point Tm of the PP is about 168°C, and the glass transition temperature Tg is about -10°C.

[0112] The preparation process of the hollow fiber membrane for degassing using the above PP as raw material includes the following process steps:

[0113] S1, spinning, put the above PP into the extruder for melt mixing, melt mixing includes melting, mixing and metering in sequence, and the temperatures are set to 165°C, 200°C and 205°C respectively. After melt mixing, the molten material is extruded into fibers, and a vertical downward spinning extrusion method is adopted. A hollow die is used during extrusion, and a cavity-forming fluid is injected into the hollow inner cavity of the die. In this embodiment, the cavity-forming fluid is nitrogen, and the outlet wall thickness of the material on the die is 2mm (that is, the wall thickness is 2mm when extruded into fibers). The die temperature is 190°C, and the die aspect ratio is 4. Under the action of the cavity-forming fluid, the material is extruded to form a semi-molded product with a hollow inner cavity. At this time, the semi-molded product is still in liquid state.

[0114] S2, natural cooling, the semi-molded product obtained by extruding the molten material is exposed to the air for preliminary natural cooling, and is naturally cooled until the surface temperature of the fiber is about 170°C, and the natural cooling is completed to obtain a naturally cooled semi-finished product. The natural cooling path length is controlled to be 100mm, and the temperature of the atmosphere around the semi-molded product is controlled to be 60°C, and the cooling rate of the fiber surface is about 0.2°C / mm@(150m / min).

[0115] S3, air cooling crystallization, further cooling the fiber by blowing cooling, so that the fiber undergoes cooling crystallization behavior. In this step, the speed of the cooling airflow is 40m / min, the temperature of the cooling airflow is 60°C, the wind direction of the cooling airflow is inclined toward the direction of fiber conveying, and the angle formed by the wind direction of the cooling airflow and the axis of the fiber is 50°.

[0116] It should be noted that the air-cooling crystallization in this step is divided into two sections, namely the rapid cooling zone and the slow cooling zone. The area where the cooling airflow moves along its wind direction and directly contacts the fiber is considered to be the rapid cooling zone. The cooling airflow and the fiber produce rapid heat exchange in this area, so that the surface of the fiber is rapidly cooled; the area from the fiber passing through the rapid cooling zone to the winding is considered to be the slow cooling zone. After the fiber passes through the rapid cooling zone and the slow cooling zone in turn, it is wound to obtain the nascent fiber.

[0117] After the fiber passes through the rapid cooling zone, the surface temperature drops to about 90°C, and then passes through the slow cooling zone with a path length of 8m for winding. The winding speed is 150m / min (i.e., spinning speed), and the nozzle stretch ratio is 40. The cooling rate of the fiber in the rapid cooling zone is 200°C / mm@(150m / min).

[0118] It should be noted that the angle between the cooling airflow and the fiber is different, and the width of the rapid cooling zone also changes slightly. Therefore, the boundary between the rapid cooling zone and the slow cooling zone is determined based on the cooling rate on the fiber surface. When the cooling rate on the fiber surface decreases significantly, it is considered that the fiber has entered the slow cooling zone from the rapid cooling zone.

[0119] S4, stretching to form holes, stretching to form holes includes primary shaping, cold drawing to form holes, hot drawing to expand holes and secondary shaping in sequence, that is, step S4 specifically includes the following process steps:

[0120] S41, primary setting, subjecting the wound spun fibers to a first heat setting treatment, the heat setting temperature being 130° C., the heat setting time being 30 minutes, and during the heat setting process, applying a drafting treatment to the spun fibers, and the drafting elongation being 1%. After the first heat setting treatment of the spun fibers, a heat-set semi-finished product is obtained.

[0121] S42, cold drawing to cause pores. After the primary fiber has been subjected to the first heat setting treatment, the defects in the fiber are roughly eliminated. At this time, the fiber can be cold drawn to initially produce a microporous structure in the inner layer with a higher degree of crystallinity of the fiber. In the cold drawing to cause pores stage, a single cold drawing process is adopted, with a cold drawing elongation of 30%, a cold drawing rate of 20% / min, and a cold drawing temperature of 30°C. After cold drawing, a cold drawn semi-finished product is obtained, and the line speed of the cold drawn semi-finished product is 3m / min.

[0122] S43, hot-drawing hole expansion, after the fiber is cold-drawn, the inner layer of the lamellae separates and produces a microporous structure, which can be further hot-drawn to expand the produced microporous structure. In addition, hot-drawing can further pull apart the lamellae that have not been separated during the cold-drawing process, thereby producing a larger number of microporous structures in the inner layer of the fiber. In the hot-drawing hole expansion stage, a hot-drawing process is adopted, the hot-drawing elongation is 100%, the hot-drawing rate is 2.4% / min, the hot-drawing temperature is 120°C, and the hot-drawn semi-finished product is obtained after hot-drawing. At this time, the line speed of the hot-drawn semi-finished product is 6m / min.

[0123] S44, secondary shaping, after the fiber is cold and hot drawn, the microporous structure of the inner layer is basically formed, but once the drawing force is removed, the fiber is easy to shrink, resulting in a reduction in the microporous structure or even partial closure. Therefore, the fiber needs to be heat-set for the second time after the cold and hot drawing treatment. In the second heat setting stage, the heat setting temperature is 140°C, the heat setting time is 2 minutes, and the hollow fiber membrane is obtained by natural cooling after the heat setting is completed.

[0124] Example 4

[0125] The main difference between Example 4 and Example 3 is that in step S3, the angle formed by the wind direction of the cooling airflow and the axis of the naturally cooled semi-finished product is 90°.

[0126] It should be noted that since the angle between the wind direction of the cooling airflow and the fiber is 90°, the fiber is cooled in an extremely short distance (the smaller the angle, the larger the contact area between the cooling airflow and the fiber, and correspondingly, the longer the path length in the rapid cooling zone), so the cooling rate in the rapid cooling zone is not calculated.

[0127] Example 5

[0128] The main difference between Example 5 and Example 3 is that the temperature of the secondary shaping in step S44 is 135° C., which is 5° C. different from the temperature of the primary shaping in step S41 .

[0129] Embodiment 6-8

[0130] The main difference between Examples 6-8 and Example 3 is that the process parameters of each step are different, and the process parameters of each step are recorded in the following table:

[0131]

[0132] Comparative Example

[0133] Comparative Example 1

[0134] The main difference between Comparative Example 1 and Example 3 is that in step S3, the fiber is quickly cooled by liquid cooling.

[0135] That is, step S3 of comparative example 1 includes the following process steps:

[0136] S3, liquid cooling crystallization, in this step, the cooling medium is deionized water, the temperature of the deionized water is 40°C, and the cooling path length is 1m. After the liquid cooling is completed, the fiber enters a 70°C oven for drying, and the nascent fiber is obtained after winding.

[0137] It should be noted that due to the need to degas deionized water, in order to prevent the influence of solvent residue on the quality of ultrapure water, the cooling medium can only be deionized water or ultrapure water.

[0138] Comparative Example 2

[0139] The main difference between Comparative Example 2 and Example 3 is that in step S3, by limiting the process parameters, the cooling rate of the fiber in the rapid cooling zone is controlled to be lower than 100°C / mm@(150m / min).

[0140] That is, step S3 of comparative example 2 includes the following process steps:

[0141] The fiber is further cooled by air blowing to cause cooling crystallization of the fiber. In this step, the speed of the cooling airflow is 20 m / min, the temperature of the cooling airflow is 70°C, the wind direction of the cooling airflow is inclined toward the direction of fiber conveying, and the angle formed by the wind direction of the cooling airflow and the axis of the fiber is 30°.

[0142] After the fiber passes through the rapid cooling zone, the surface temperature drops to about 120°C, and then passes through the slow cooling zone with a path length of 8m for winding, with a winding speed of 150m / min and a nozzle stretch ratio of 40. The cooling rate of the fiber in the rapid cooling zone is about 86°C / mm@(150m / min).

[0143] Comparative Example 3

[0144] The main difference between Comparative Example 3 and Example 3 is that in step S3, the fiber is not cooled by air blowing, but continues to be cooled by air cooling.

[0145] That is, step S3 of comparative example 3 includes the following process steps:

[0146] The fiber was further cooled by natural cooling until the surface temperature of the fiber was about 80°C. During this process, the path length of natural cooling was controlled to be 8m, the temperature of the atmosphere around the semi-molded product was controlled to be 60°C, and the cooling rate of the fiber surface was about 0.011°C / mm@(150m / min).

[0147] Performance testing methods and performance testing data

[0148] 1. Gas flux detection

[0149] The hollow fiber membranes prepared in the examples or comparative examples were used as raw materials to assemble a membrane with an area of ​​0.1 m 2 The component is used as a sample to detect the gas flux.

[0150] Gases with a pressure of 0.1 MPa were introduced into the inlet of the component. The gases were oxygen, nitrogen and carbon dioxide respectively. The outlet of the component was connected to a flow meter to record the gas flux of the component per unit time.

[0151] Generally speaking, the larger the gas flux, the better the degassing effect of the component.

[0152] 2. Degassing efficiency and damage sensitivity

[0153] 2.1 Deoxygenation efficiency

[0154] The hollow fiber membranes prepared in the examples or comparative examples were used as raw materials to assemble a membrane having an area of ​​0.65 m 2The components are connected with the dissolved oxygen meter, water circuit and components for testing. The water circuit is used to transport the degassed liquid, the components are used to degas the degassed liquid, and the dissolved oxygen meter is used to detect the oxygen content of the degassed liquid after degassing. The degassed liquid is deionized water and the temperature of the degassed liquid is 25°C. The inside of the membrane is vacuum purged.

[0155] Step 1: Detect the initial oxygen content of the degassed liquid. Pump the degassed liquid into the water circuit. At this time, turn off the vacuum equipment to make the inner side of the membrane at normal pressure. The degassed liquid passes through the assembly (without degassing) and then the dissolved oxygen meter. Keep the flow rate of the degassed liquid into the dissolved oxygen meter at about 1.8 GLH. Observe the changes in the dissolved oxygen reading on the dissolved oxygen meter in real time. After the reading of the dissolved oxygen meter stabilizes (the reading of the dissolved oxygen meter changes by less than 1% within 5 minutes), read the dissolved oxygen reading on the dissolved oxygen meter. 始 .

[0156] Step 2: Detect the final oxygen content of the degassed liquid after degassing. On the basis of step 1, turn on the vacuum equipment to vacuum purge the inner layer of the membrane to degas the degassed liquid. During the vacuum purge, keep the vacuum reading at -0.094MPa (50torr). Observe the changes in the dissolved oxygen reading on the dissolved oxygen meter in real time. When the reading of the dissolved oxygen meter stabilizes (the reading of the dissolved oxygen meter changes by less than 1% within 5 minutes), the degassing is considered to have reached equilibrium. Read the dissolved oxygen reading on the dissolved oxygen meter. 终 The deoxidation efficiency is calculated by the following formula:

[0157]

[0158] 2.2 Water vapor transmission rate

[0159] On the basis of test method 2.1, after degassing begins, the system is run for 4 hours, and the flow rate s of the degassed liquid in the water path is recorded within 4 hours. After the operation is completed, the condensed water in the vacuum equipment is collected, the volume v of the condensed water is measured, and the water vapor transmission rate is calculated according to the following formula:

[0160]

[0161] 2.3 Acid damage sensitivity

[0162] On the basis of test method 2.1, the degassing liquid was replaced with a hydrochloric acid solution with a concentration of 5 mol / L. The condition of the component was observed every 4 hours. When leakage occurred on the inner side of the membrane, the component was considered to be breached and lost its degassing ability. The time when the component was breached was recorded.

[0163] 2.4 Alkali damage sensitivity

[0164] On the basis of test method 2.1, the degassing liquid was replaced with a sodium hydroxide solution with a concentration of 5 mol / L. The condition of the component was observed every 4 hours. When leakage occurred on the inner side of the membrane, the component was considered to be breached and lost its degassing ability. The time when the component was breached was recorded.

[0165] 2.5 Resistance to wetting damage sensitivity

[0166] On the basis of test method 2.1, the degassing liquid was replaced with 100% n-butanol (surface tension of 24.6 dynes), and the component was observed every 4 hours. When leakage occurred on the inner side of the membrane, the component was considered to be breached and lost its degassing ability. The time when the component was breached was recorded.

[0167] 3. Mechanical properties

[0168] The tensile properties of the hollow fiber membranes prepared in the embodiments and comparative examples were tested. The two ends of the hollow fiber membranes were clamped with chucks with a distance of 5 cm between the two ends (i.e., the actual test length of the hollow fiber membrane was 5 cm), and the tensile strength and elongation at break of the hollow fiber membranes were tested.

[0169] 3.1 Tensile strength

[0170] Tensile Strength:

[0171] In the formula: σ—tensile strength; Fb—maximum force when breaking; So—original cross-sectional area of ​​the specimen; “specimen area S” is used in the instrument to represent it.

[0172] 3.2 Elongation at break

[0173] Elongation at break:

[0174] Where: e is the elongation at break; △L is the length increment between the gauge lengths of the specimen; L is the gauge length of the specimen.

[0175] The morphological characteristics of each embodiment and comparative example are shown in Table 1:

[0176] Table 1: Film structure morphology characteristics of each embodiment and comparative example

[0177]

[0178]

[0179] It should be noted that the embodiments in Table 1 with an outer surface porosity of 0 do not mean that there is no microporous structure on the outer surface at all, but rather that the size and number of the microporous structure are almost negligible, and therefore recorded as 0.

[0180] In Table 1, dimensional stability refers to the outer diameter of the hollow fiber membranes prepared in each embodiment or comparative example. The outer diameter of each hollow fiber membrane is measured 3 times, with an interval of 20 cm between each measurement. The maximum value of the outer diameter is recorded as d max , record the smallest outer diameter as d min , the dimensional change rate is calculated according to the following formula:

[0181]

[0182] The performance test data of each embodiment and comparative example are shown in Table 2:

[0183] Table 2 Performance test data of each embodiment and comparative example membrane

[0184]

[0185]

[0186] In Table 2, the water vapor transmission rate data of some embodiments are not recorded. This is because only a very small amount of condensed water can be collected in the vacuum equipment, and the water vapor transmission rate is too small and therefore not recorded.

[0187] in conclusion

[0188] By comparing the technical solutions of Examples 1-3 and the relevant data of Table 1-2, it is not difficult to see that compared with PE and PMP, the hollow fiber membrane of PP material has a significantly larger gas flux. However, the hollow fiber membrane of PE and PMP material has a higher gas separation rate. Therefore, the appropriate polyolefin material can be selected according to the needs.

[0189] By comparing the technical solutions of Example 3 and Comparative Example 1 and the relevant data of Tables 1-2, it is not difficult to see that the rapid cooling method with coolant not only ultimately leads to the formation of a fiber cortex, but also the porosity of the inner layer of the fiber is also very low due to the rapid cooling of the interior of the fiber, which ultimately leads to a serious decrease in the degassing effect of the hollow fiber membrane.

[0190] By comparing the technical solutions of Example 3 and Comparative Example 2 and the relevant data of Tables 1-2, it is not difficult to see that if a sufficiently fast cooling rate cannot be provided during the rapid air-cooling crystallization stage, although the obtained hollow fiber membrane has a reduced cortical thickness and better degassing performance, the damage sensitivity of the hollow fiber membrane is significantly improved, which leads to a significant decrease in the service life of the hollow fiber membrane.

[0191] By comparing the technical solutions of Example 3 and Comparative Example 3 and the relevant data of Tables 1-2, it is not difficult to see that compared with the hollow fiber membrane with an inner and outer through-membrane pore structure, the hollow fiber membrane with a dense skin layer and a porous inner layer specific to the present application has a slightly decreased degassing effect, but has a significantly longer service life and a lower water vapor permeability.

[0192] By further comparing the technical solutions of Example 6 and Comparative Example 3 and the relevant data of Table 1-2, it is not difficult to see that as long as the thickness of the hollow fiber membrane skin and the pore structure of the inner layer are well controlled, the degassing effect can be only slightly reduced while significantly improving the service life of the hollow fiber membrane and reducing the water vapor permeability.

[0193] By comparing the technical solutions of Example 3 and Example 4 and the relevant data of Table 1-2, it is not difficult to see that the cooling airflow during air blowing cooling needs to form a certain angle with the fiber, so that a significantly better membrane pore structure can be obtained.

[0194] By comparing the technical solutions of Example 3 and Example 5 and the relevant data of Table 1-2, it is not difficult to see that there needs to be a certain temperature difference between the temperature during the first shaping treatment and the temperature during the second shaping treatment. If the temperature difference between the two is small (less than 10°C), the second shaping treatment will most likely not be able to eliminate the stress of the fiber well, resulting in fiber shrinkage, pore structure closure, fiber size enlargement, and decreased porosity.

[0195] By comparing the technical solutions of Example 3 and Example 6 and the relevant data of Table 1-2, it is not difficult to see that by controlling the cooling rate of the fiber in the rapid air cooling stage, the cortical thickness and inner pore structure of the hollow fiber membrane can be adjusted. Thus, the degassing performance of the hollow fiber membrane is significantly improved without affecting (or having a very small impact on) the service life of the hollow fiber membrane.

[0196] By comparing the technical solutions of Example 3 and Examples 7-8 and the relevant data of Table 1-2, whether the cooling rate of the fiber in the rapid air cooling stage is too high or too low, it will lead to a decrease in the service life or degassing performance of the finally obtained hollow fiber membrane.

[0197] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A process for preparing a polyolefin hollow fiber membrane for degassing, characterized in that: The process steps include: S1, spinning, melt-extrude the polyolefin material to form a semi-molded product with a hollow inner cavity under the action of a cavity-forming fluid, wherein the polyolefin material is at least one of PP, PE and PMP, and the melting point of the polyolefin material is Tm and the glass transition temperature is Tg; S2, natural cooling, preliminarily cooling the semi-formed product obtained in step S1 by natural cooling to obtain a naturally cooled semi-finished product; the surface temperature of the naturally cooled semi-finished product obtained after natural cooling drops to Tm~(Tm+20)°C; S3, air-cooling crystallization, cooling and crystallizing the naturally cooled semi-finished product obtained in step S2 by means of air-blowing cooling, the air-cooling crystallization includes a rapid cooling zone and a slow cooling zone, the naturally cooled semi-finished product is rolled up after passing through the rapid cooling zone and the slow cooling zone, to obtain spun fibers; wherein the surface temperature of the naturally cooled semi-finished product is reduced to (Tg+80)~(Tg+120)°C after passing through the rapid cooling zone, and the cooling rate of the naturally cooled semi-finished product in the rapid cooling zone is not less than 100°C / mm@(100~200)m / min; S4, stretching to form holes, the primary fibers obtained in step S3 are subjected to primary shaping, cold-drawing to form holes, hot-drawing to expand holes, and secondary shaping in sequence to obtain a hollow fiber membrane.

2. The process for preparing a polyolefin hollow fiber membrane for degassing according to claim 1, characterized in that: In the step S1, The die temperature during melt extrusion is (Tm+10)~(Tm+70)℃; The die head aspect ratio during spinning is 2 to 5; The crystallinity of the polyolefin material is not less than 40%.

3. The process for preparing a polyolefin hollow fiber membrane for degassing according to claim 1, characterized in that: In the step S2, The path length for natural cooling is 30 to 1000 mm; The atmosphere during natural cooling is air or nitrogen, and the atmosphere temperature during natural cooling is 40-70°C; During natural cooling, the cooling rate of the semi-molded product surface is (0.05~0.6)℃ / mm@(100~200)m / min.

4. The process for preparing a polyolefin hollow fiber membrane for degassing according to claim 1, characterized in that: In the step S1, The polyolefin material is PP; The isotacticity of PP is not less than 95%; The melt index of PP is 1-7 g / min@(190°C, 5 kg); The crystallinity of PP is 45-70%; The wall thickness of the semi-molded product is 0.5 to 3 mm.

5. The process for preparing a polyolefin hollow fiber membrane for degassing according to claim 4, characterized in that: In the step S1, the die temperature during melt extrusion is 180-200°C; In the step S2, the surface temperature of the naturally cooled semi-finished product obtained after natural cooling is 168-178°C; In step S3, the surface temperature of the naturally cooled semi-finished product after passing through the rapid cooling zone is 80-100°C.

6. The process for preparing a polyolefin hollow fiber membrane for degassing according to claim 4, characterized in that: In the step S3, The winding speed is 100-200m / min; The nozzle stretch ratio is 10-50.

7. The process for preparing a polyolefin hollow fiber membrane for degassing according to claim 6, characterized in that: In the step S3, The speed of the cooling airflow is 25-35% of the winding speed; The temperature of the cooling air flow is 40-70°C.

8. The process for preparing a polyolefin hollow fiber membrane for degassing according to claim 7, characterized in that: In the step S3, The wind direction of the cooling airflow is inclined along the conveying direction of the naturally cooled semi-finished product; The angle formed by the wind direction of the cooling airflow and the axis of the naturally cooled semi-finished product is 30 to 70°; The path length of the slow cooling zone is 4 to 8 m.

9. The process for preparing a polyolefin hollow fiber membrane for degassing according to claim 1, characterized in that: In the step S4, The cold drawing rate is (10-30)% / min; The cold drawing elongation is 20-40%; Cold drawing temperature is (Tg-30)~(Tg+80)℃; The hot drawing rate is not higher than 15% of the cold drawing rate; The hot stretching elongation is 2 to 6 times that of the cold stretching elongation; The hot drawing temperature is (Tm-60)~(Tm-30)℃.

10. The process for preparing a polyolefin hollow fiber membrane for degassing according to claim 9, characterized in that: In the step S4, The primary setting temperature is (Tm-60)~(Tm-20)℃; The time for one setting is 25 to 35 minutes; The primary fibers are subjected to a drafting process during the primary shaping process, and the drafting elongation is 0.5 to 2%; The temperature of the secondary setting temperature is higher than the temperature of the primary setting temperature, and the difference between the two is 10-20°C; The secondary shaping time is 0.5 to 3 minutes.